Duloxetine improves cancer-associated pain in a mouse model of pancreatic cancer through stimulation of noradrenaline pathway and its antitumor effects. Issue 12 (December 2020) - Kajiwara, Ichie; Sano, Makoto; Ichimaru, Yoshimi; Oshima, Yukino; Kitajima, Osamu; Hao, Hiroyuki; Masamune, Atsushi; Kim, Jinsuk; Ishii, Yukimoto; Ijichi, Hideaki; Suzuki, Takahiro
Abstract : Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive cancer with a poor prognosis. Patients with inoperative PDAC require effective chemotherapy and pain control to increase their quality of life. We investigated whether duloxetine, a serotonin–noradrenaline reuptake inhibitor, improves quality of life in a KPPC ( LSL-Kras G12D/+ ;Trp53 flox/flox ;Pdx1-cre ) mouse model of PDAC. Six-week-old KPPC mice were orally administered 4 mg/kg/d duloxetine (n = 12); 4 mg/kg/d duloxetine with 0.15 mg/kg/d atipamezole, a synthetic α2 adrenergic receptor antagonist (n = 9); or vehicle water (n = 11). Body weight and food intake were measured daily, and cancer pain was evaluated by the hunching score and mouse grimace scale. At the endpoint, the tumor status, angiogenesis, and immunoinflammatory condition were analyzed. The pain level using the hunching and mouse grimace scale scores improved by duloxetine in KPPC mice ( P < 0.01), whereas the scores that had been reduced by duloxetine were elevated by administration of atipamezole. Kaplan–Meier analysis demonstrated that duloxetine-treated mice had significantly prolonged survival ( P < 0.05) with delayed appetite loss, cachexia, and body weight loss. Duloxetine inhibited the proliferation of PDAC cells and cancer-associated fibroblasts in vivo with a shift into an antitumor immunoinflammatory condition and the corresponding plasma cytokine levels. The migrative/invasive potentials of PDAC were inhibited by duloxetine in vitro. Meanwhile, atipamezole did not inhibit the antitumor effects of duloxetine in vitro and in vivo. Therefore, our results indicate that duloxetine mainly improves cancer-associated pain by enhancement of the noradrenergic pathway rather than the serotonergic pathway, whereas duloxetine modulates antitumor effects on PDAC without involvement of the noradrenergic pathway. Abstract : Supplemental Digital Content is Available in the Text.Duloxetine improves cancer-associated pain in a mouse model of pancreatic cancer through stimulation of noradrenaline pathway and its antitumor effects.